Nesting features of blackbird (Turdus merula) in urban green spaces in Minsk - Sakhvon, Vital V. (Journal of the Belarusian State University. Ecology, 2022)
Synurbic populations of birds are characterized by specific features that differ from those of wild populations of the same species, which is the result of adaptation to living in cities. The paper analyses some parameters of breeding of the Blackbird (Turdus merula) in two park in Minsk and compares them with the breeding biology of wild Blackbirds in natural habitats. During the years 2015-2017 and 2019-2021, 74 nests of urban Blackbird were obtained. For comparison, data on 245 nest of this species in natural landscapes were used.As a result, it was found that the nest selection in urban Blackbirds remains similar to wild Blackbirds in forests, and the differences are explained by the peculiarities of forestry activities carried out in urban parks. More than 74 % of all nests were built in the undergrowth layer, while most of the nests were located on the Norway spruce (59.72 %). A majority of urban Blackbirds started laying first eggs relatively later (from 21.04 to 10.05) than forest birds (from 11.04 to 30.04), which most likely results from the adaptation of birds to a significant recreational load from humans during the period when the trees have not come into leaf yet. Nevertheless, no differences were found in the average clutch size between urban (4.17 ± 0.72 eggs) and forest (4.51 ± 0.64 eggs) birds. The low breeding success of the Blackbird (39.4 %) in the urbanized area testifies to the fact that the homeostasis of the relatively high number of the urban Blackbird population in Minsk is most likely maintained due to the constant influx of individuals from local suburban forests.